Spectacular Effect of Massive Facial Angiofibromas Removal With a Carbon Dioxide Laser as a Manifestation of a Tuberous Sclerosis Complex: TSC angiofibromas removal with CO2 laser - Adam, BorzÄ™cki; Katarzyna, Chyl-Surdacka; Turska, Monika (Journal of Lasers in Medical Sciences, 2021)
Introduction: Tuberous sclerosis complex (TSC) is a rare, genetic disease that leads to neurological, cardiological, nephrological, ophthalmic, pulmonary, and skin disorders. Case Presentation: Here, we describe a case of a 64-year-old man with the presence of giant angiofibromas located on his chin and nasolabial folds which caused inconvenience and unaesthetic appearance. All angiofibromas were removed with the use of a CO2 laser. The patient was extremely satisfied with the obtained result. No side effects were observed after a 6-month follow-up. Conclusion: Despite the fact that giant facial angiofibromas may be troublesome not only for patients but also for medical doctors, adequate CO2 laser usage with local anesthesia and control of massive bleeding is a promising treatment option for patients with TSC. DOI: 10.34172/jlms.2021.24